Reduced mismatch negativity in children and adolescents with autism spectrum disorder is associated with their impaired adaptive functioning. Issue 8 (12th May 2022) - Lassen, Jonathan; Oranje, Bob; Vestergaard, Martin; Foldager, Malene; Kjær, Troels W.; Arnfred, Sidse; Aggernæs, Bodil
Abstract: Children and adolescents on the autism spectrum display sensory disturbances, rigid and repetitive behavior, social communication problems and a high prevalence of impaired adaptive functioning. Autism is associated with slowed behavioral and neural habituation to repeated sensory input and decreased responses to sensory deviations. Mismatch negativity (MMN) reflects a pre‐attentive difference in the neural response to sensory deviations relative to regularities and studies overall suggest that children and adolescents with autism tend to have smaller MMN. However, it remains unclear whether reduced MMN in autism is coupled to severity of specific autistic symptoms or more generally to lower level of adaptive functioning. To address these questions, the present study used electroencephalography (EEG) to assess whether auditory MMN in 59 children and adolescents with autism aged 7–14 years compared to 59 typically developing children and adolescents were related to specific autistic symptoms or level in adaptive functioning. As hypothesized, the autism group had a lower MMN amplitude than controls. Smaller MMN amplitudes were specifically associated with lower adaptive functioning in the autistic subjects but not in controls while no apparent relationships were observed with autistic‐like social interaction and communication problems, atypical language, rigidity, stereotypy or sensory sensitivity symptoms. Our findings indicate that a blunted response to changes in sensory input may underlie or contribute to the generalized difficulties with adapting to daily life circumstances seen in children and adolescents with autism. Lay Summary: Children and adolescents on the autism spectrum have a high prevalence of impaired adaptive functioning. Neuroimaging studies have reported that children and adolescents with autism display attenuated brain activity when discriminating sensory input. However, it is unknown whether this attenuation is related to autistic symptoms and/or adaptive functioning. The present study used electroencephalogram (EEG) to show that attenuated brain response in discrimination of novel compared to repetitive sounds in children and adolescents with autism is related to their impaired adaptive functioning.